A constituição e a administração da identidade de gênero homossexual masculino assumida no trabalho e a sua articulação com o consumo - Santos, Marcia Pereira (2015)
This study aimed to describe the male homosexual identity constitution process assumed in the organizational environment and identify, based on the narrative of homosexuals at work, as consumption islinked to the administration of this identity. The theoretical framework was based on the deepening of the following topics: identity(according to Giddens, 2002; Bauman, 2005; Hall, 2006); homosexuality (Foucault, 1988; Weinstein, 1998; Irigaray, 2007 and 2011; Pereira, 2009); work (Bendassolli, 2006; Gaulejac, 2007; Dejours,1994 and 2007;Senett, 2009); consumer culture (Feathersone, 2007; Slater, 2001; McCracken, 2003;Arnoult& Thompson, 2005); stigma (Goffman, 1998 and 2002); and ontological security (Giddens, 2002). This research is important in that it encourages the construction of equal consciousness, organizational environment, assumed due to homosexual men. It sought answers in order to create conditions for the implementation of effective mechanisms for equal rights in labor relations homosexuals, objectively promoting the discussion of reality and the adverse conditions of male homosexuals in the organizational. There were 15 nonstructured interviews and narratives in depth (according to Bauer & Gaskell, 2002) focusing on the life history of these subjects. In the analysis of narratives, finally, we found that there is a suggested style, proposed by the Organization, and considered as heteronormative standard style. Male homosexuals use the symbolic meanings of possessions as mechanisms that meet a standardized organizational style. They adopt this style and thus resume the process of building and rebuilding their self and their homosexual identity assumed at work.